2009
DOI: 10.4049/jimmunol.0803044
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial DNA Activates Endothelial Cells and Promotes Neutrophil Adherence through TLR9 Signaling

Abstract: TLR9 detects bacterial DNA (CpG DNA) and elicits both innate and adoptive immunity. Recent evidence indicates that TLR9 is expressed in more diverse cell types than initially thought. In this study, we report that HUVECs constitutively express TLR9 and selectively recognize unmethylated CpG motifs in bacterial DNA and synthetic immune stimulatory CpG oligodeoxynucleotides. HUVECs respond to CpG DNA with rapid phosphorylation of IκB-α and NF-κB-mediated gene transcription and surface expression of the adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 54 publications
5
84
1
4
Order By: Relevance
“…Recent studies reported that CD14 is involved in the activation of TLR2, TLR3, TLR7, and TLR9, because CD14-null mice and CD14-deficient cells display less inflammatory response to the specific ligands of these TLRs (5-7). We also observed that addition of rCD14 to endothelial cells, which do not express the membrane form of CD14 but do express TLR4 and TLR9 (8,30,31), markedly increased IL-6 secretion by HUVECs after LPS or CpG-ODN challenge. rTMD23 not only inhibited LPS-induced IL-6 secretion by HUVECs, it also suppressed CpG-ODN-induced IL-6 production, suggesting that the anti-inflammatory capability of rTMD23 occurs through specific suppression of CD14 functioning.…”
Section: I424asupporting
confidence: 51%
“…Recent studies reported that CD14 is involved in the activation of TLR2, TLR3, TLR7, and TLR9, because CD14-null mice and CD14-deficient cells display less inflammatory response to the specific ligands of these TLRs (5-7). We also observed that addition of rCD14 to endothelial cells, which do not express the membrane form of CD14 but do express TLR4 and TLR9 (8,30,31), markedly increased IL-6 secretion by HUVECs after LPS or CpG-ODN challenge. rTMD23 not only inhibited LPS-induced IL-6 secretion by HUVECs, it also suppressed CpG-ODN-induced IL-6 production, suggesting that the anti-inflammatory capability of rTMD23 occurs through specific suppression of CD14 functioning.…”
Section: I424asupporting
confidence: 51%
“…CpG is known to activate endothelial cells leading to increased expression of adhesion molecules (e-selectin, p-selectin, ICAM, VCAM) and chemokines (IL-8 and MCP-1). 7 Additionally, activated endothelial cells are known to secrete and transport TNF. 22 LPS-stimulated brain endothelial cells in vitro have been shown to secrete TNF in a polarized manner preferentially releasing TNF on the luminal side and into the peripheral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…TLR9 is expressed on a wide variety of cell types both in the brain (microglia, neurons, astrocytes, cerebral vascular endothelium) and on hematopoietic cells in the periphery. [7][8][9][10][11] Thus, it is unknown whether CpG preconditioning activates TLR9 on cells within the brain or whether TLR9 signaling in systemic circulating cells is required to elicit the neuroprotective phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…89,90 Human umbilical vein endothelial cells (HUVECs) express TLR3 and TLR9. [91][92][93] Human dermal microvascular endothelial cells express MR. 94 Besides, Galection-3 was detected on cultured endothelial cells. 95 The expression of Dectin-1 on endothelial cells is controversial.…”
Section: Prrs Of Endothelial Cellsmentioning
confidence: 99%